(untitled) (Global Journal of Human-Social Science, 2016)
This article has the challenge to discuss the ambivalent relationship between arrival in the power through concessions to conservative sectors of society foreshadowed in the letter to the Brazilian people and the discourse of the struggle for power based on the argument of search for relevant social gains in which part of the Brazilian left is immersed since the victory of Workers Party in 2002 in the presidential election in Brazil Here are the actors and the main events that give basis for the proposed discussion To give theoretical basis we analyze the case in light of Marxian theory seeking to enable reflections on the question some sectors of the Brazilian left do not perform structural failure in the power system in the country made the social reformism and economic conservative as a search of power articulating the cooling of tensions between the classes We conclude that the proposed reformism is a mechanism not completely abandoned the search for social justice proposals however it is the exclusion of any possibility of structural changes whether the values in the order or in the structure of domination